Myocardial tissue Doppler velocities in fetuses with hypoplastic left heart syndrome - Himesh V Vyas; Benjamin W Eidem; Frank Cetta; Ganesh Acharya; James Huhta; David Roberson; Bettina Cuneo (Wolters Kluwer Medknow Publications, 2011)
Background : Tissue Doppler Imaging (TDI) is a sensitive index of myocardial function. Its role in the fetus has not been extensively evaluated. Objective: To compare myocardial tissue Doppler velocities in fetuses with hypoplastic left heart syndrome (HLHS) to those of normal fetuses (matched for gestational age.) Methods: Cross-sectional retrospective study conducted at 2 large perinatal centers (2003-2007). Fetuses with HLHS ( n = 13) were compared with normal fetuses ( n = 207) in 5 gestational age groups. TDI data included peak systolic (s'), peak early (e'), and late diastolic velocities (a'). Linear regression was used to compare TDI parameters in fetuses with HLHS to normal fetuses matched for gestational age. Results: Fetuses with HLHS had significantly reduced lateral tricuspid annular e' as compared to normal fetuses. Both normal fetuses and those with HLHS had linear increase in TDI velocities with advancing gestational age. Conclusions: TDI velocities are abnormal in fetuses with HLHS. TDI can be useful in serial follow-up of cardiac function in fetuses with HLHS.